Use of standardised outcome measures among physiotherapists in French-speaking sub-Saharan Africa - Abdoulaye Sawadogo; Emmanuel Segnon Sogbossi; Gauthier J. Everard; Toussaint Kpadonou; Charles Sèbiyo Batcho (AOSIS, 2024)
Background: The use of standardised assessment tools is a fundamental aspect of good clinical practice. However, to our knowledge, no study has documented the use of standardised assessment tools in physiotherapy in French-speaking sub-Saharan Africa. Objectives: Documenting the use of standardised outcome measures in physiotherapy in French-speaking sub-Saharan Africa. Method: Our cross-sectional survey used an online self-questionnaire on facilitators and barriers to the use of standardised outcome measures, distributed to physiotherapists in French-speaking sub-Saharan Africa. Results: A total of 241 physiotherapists working in French-speaking sub-Saharan Africa responded to the survey. The most represented countries were Benin (36.9%), Cameroon (14.1%), and Burkina Faso (10.8%). Although 99% of participants reported using standardised outcome measures, only 27% of the respondents used them systematically (all the time). The most reported facilitators included the recognition that standardised outcome measures help to determine whether treatment is effective, help to guide care, and improve communication with patients. The most significant barriers were the lack of time, unavailability of the standardised outcome measures, and non-sensitivity of measures to patients' cultural and ethnic concerns. There was a higher proportion of use in the middle age group (30-40) (p = 0.02) and a lower proportion of use in physiotherapists simultaneously working in public and private sectors (p = 0.05). Conclusion: Standardised outcome measures are still not widely used by physiotherapists in French-speaking sub-Saharan Africa. Clinical implications: The perceived barriers and facilitators could help to develop strategies to improve the systematic use of outcome measures in French-speaking sub-Saharan Africa.